Identification and Biological Control of Neopestalotiopsis chrysea Causing Leaf Spot Disease in Ocimum sanctum L. (Plant Tissue Culture and Biotechnology, 2026)
Neopestalotiopsis chrysea has emerged as an aggressive pathogen in nurseries and fields, causing concerns among medicinal plant growers. The purpose of the present study was to isolate, identify, and characterize the pathogenic fungus associated with leaf spot disease of tulsi (Ocimum sanctum L.), and to investigate as well as into the antagonistic effects of specific plant extracts and selected biocontrol agents, such as Trichoderma spp., as alternatives to conventional fungicides. Neopestalotiopsis chrysea causes leaf spot symptoms in Ocimum sanctum during its early and mature phases. The polymerase chain reaction (PCR) results showed an internal transcribed spacer (ITS) region of 557 bp in    N. chrysea isolate JUF0129 and its GenBank accession number PX376321.1, and a BLAST search indicated a 100% sequence match with N. chrysea (PV866874.1). Pathogenicity testing confirmed the correlation between the fungus and disease symptoms in greenhouse environments. Mycelial growth of N. chrysea was highest on the potato dextrose agar (PDA) medium (55.33 mm), followed by the malt extract agar (MEA) medium, and lowest on the yeast extract agar (YEA) medium (31.11 mm). N. chrysea grew and developed mycelially best at 25°C and pH 7. Against the mycelial growth and development of N. chrysea, Trichoderma atroviridae exhibited the highest mycelial growth inhibition (68.94%), followed by T. virens (63.82%). The antifungal properties of Andrographis paniculata are more effective than those of Lawsonia inermis. A. paniculata exhibited the maximum inhibition (60.85%) at the highest concentration (30%), which was much more than that of L. inermis. Fungal growth is considerably inhibited as the treatment concentration increases. This study provides a valuable resource for future investigation and the development of effective environment-friendly disease management strategies against pathogenic fungi.Plant Tissue Cult. & Biotech. 36(1): 79-89, 2026 (June)